Study on Electron-Induced Surface Plasmon Coupling with Quantum Well Using a Perturbation Method - Yifan Chen; Yulong Feng; Zhizhong Chen; Fei Jiao; Jinglin Zhan; Yiyong Chen; Jingxin Nie; Zuojian Pan; Xiangning Kang; Shunfeng Li; Qi Wang; Shulin Zhang; et al. (Nanomaterials, 2020)
Ag nanoparticles (NPs) are filled in a photonic crystal (PhC) hole array on green light emitting diodes (LEDs). The localized surface plasmon (LSP)–quantum well (QW) coupling effect is studied by measuring the cathodoluminescence (CL) spectra impinging at the specific spots on the Ag NPs. Twenty-six percent and fifty-two percent enhancements of the CL intensities are obtained at the center and edge of the Ag NP, respectively, compared to the result that the electron-beam (e-beam) excites the QW directly. To illustrate the coupling process of the three-body system of e-beam–LSP–QW, a perturbation theory combining a three-dimensional (3D) finite difference time domain (FDTD) simulation is put forward. The effects of the polarization orientation of the dipole and the field symmetry of the LSP on the LSP–QW coupling are also discussed.